2022
DOI: 10.1001/jamadermatol.2022.3975
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox Infection

Abstract: This case report describes multiple subcentimeter vesicles and papulovesicules with central necrosis surrounding the anal opening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The process is outlined in the PRISMA flow diagram labelled figure 1. Among the 33 papers, 14 studies were case studies on either one patient or a group of patients,44–46 48 51–60 3 studies were prospective43 47 61 and 9 studies were retrospective 13 40 41 62–67. Seven studies did not meet the study design for the three categories 42 68–73.…”
Section: Resultsmentioning
confidence: 99%
“…The process is outlined in the PRISMA flow diagram labelled figure 1. Among the 33 papers, 14 studies were case studies on either one patient or a group of patients,44–46 48 51–60 3 studies were prospective43 47 61 and 9 studies were retrospective 13 40 41 62–67. Seven studies did not meet the study design for the three categories 42 68–73.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of cases of mpox infection reasonably concluded by review authors to have resulted from a single transmission route occurred through direct physical sexual contact (13, 14, 18, 20, 22, 23, 25, 26, 27, 33, 34, 36, 37, 39, 40, 42, 44, 45, 47, 48, 51, 58, 59, 60, 61, 63, 64, 65, 67, 68, 71, 72, 78, 79, 83, 85, 86, 87, 88, 92, 93, 96, 97, 103, 104, 105, 106, 107, 109, 110, 111, 112, 114, 115, 119, 126) (Table 4). Where they could identify a single route of human-to-human transmission resulting in mpox infection, investigators reported no cases in which inhalation could reasonably have been the singular mode of mpox virus transmission (Table 4).…”
Section: Number Of Incident Cases By Route Of Transmissionmentioning
confidence: 98%
“…114 studies reported cases of human-to-human mpox as a result of transmission (13126). 39 studies were conducted prior to the 2022 outbreak (15, 16, 19, 21, 24, 31, 32, 35, 38, 43, 46, 49, 50, 53, 54, 55, 56, 62, 66, 69, 73, 74, 76, 77, 80, 81, 82, 83, 95, 99, 100, 101, 102, 116, 117, 120, 123, 124, 125) and 75 studies were published during 2022 (13, 14, 17, 18, 20, 22, 23, 25, 26, 27, 28, 29, 30, 33, 34, 36, 37, 39, 40, 41, 42, 44, 45, 47, 48, 51, 52, 57, 58, 59, 60, 61, 63, 64, 65, 67, 68, 70, 71, 72, 75, 78, 79, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, <...…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 By contrast, most patients of the new outbreak are men self-identified as men who have sex with men, presenting usually with a mild disease, with predominant genital and perianal involvement, consistent with sexual exposure as has been reported, and raising the possibility of sexual transmission as the main route of spreading. 3,4 The diagnosis of monkeypox is confirmed by the detection of virus DNA by PCR in skin lesions, but it can also be detected in blood, nasopharyngeal, urine, semen, or rectal samples. Skin biopsy is another diagnostic tool.…”
mentioning
confidence: 99%